Star reporter - Escott, John.; Erasmus, John. (Oxford : Oxford University Press, 2000)
'There's a new girl in town,' says Joe, and soon Steve is out looking for her. Marietta is easy to find in a small town, but every time he sees her something goes wrong... and his day goes from bad to worse.
Keywords: Readers; Reading comprehension -- Problems, exercises, etc; Stage books